2011
DOI: 10.1177/0022034511424154
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Chlorhexidine Varnish for the Prevention of Adult Caries

Abstract: The Prevention of Adult Caries Study, an NIDCR-funded multicenter, double-blind, randomized clinical trial, enrolled 983 adults (aged 18-80 yrs) at high risk for developing caries (20 or more intact teeth and 2 or more lesions at screening) to test the efficacy of a chlorhexidine diacetate 10% weight per volume (w/v) dental coating (CHX). We excluded participants for whom the study treatment was contraindicated or whose health might affect outcomes or ability to complete the study. Participants were randomly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 17 publications
0
37
0
Order By: Relevance
“…In addition to a binary indicator for male gender, we defined acidic drink use as low (0–1 twelve ounce acidic drinks per day), medium (2–4 acidic drinks per day, and high (more than four acidic drinks per day); daily flossing as flossing one or more times per day; frequency of routine dental care as high (two or more times/year), medium (2–5 times in the past 5 years), and low (less often); xerostomia risk as high (use of medications for mood disorders), medium (use of medications for high blood pressure or heart trouble, but not mood disorders), and low (none of these medications); high baseline D2 score (prior to needed restoration for randomization) as two or more cavitated (D2) lesions; and regular tobacco use as smoking or other use of tobacco products on a regular basis. Given the lack of a significant effect of the chlorhexidine on either the D12FS or the D2FS increments , we did not include an indicator of treatment assignment in these analyses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to a binary indicator for male gender, we defined acidic drink use as low (0–1 twelve ounce acidic drinks per day), medium (2–4 acidic drinks per day, and high (more than four acidic drinks per day); daily flossing as flossing one or more times per day; frequency of routine dental care as high (two or more times/year), medium (2–5 times in the past 5 years), and low (less often); xerostomia risk as high (use of medications for mood disorders), medium (use of medications for high blood pressure or heart trouble, but not mood disorders), and low (none of these medications); high baseline D2 score (prior to needed restoration for randomization) as two or more cavitated (D2) lesions; and regular tobacco use as smoking or other use of tobacco products on a regular basis. Given the lack of a significant effect of the chlorhexidine on either the D12FS or the D2FS increments , we did not include an indicator of treatment assignment in these analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The Prevention of Adult Caries Study (PACS) was a 13‐month randomized clinical trial designed to test the effect of a chlorhexidine dental coating on the development of cavitated and noncavitated lesions in high risk adults aged 18–80 . This study reports on a secondary analysis of PACS data to determine what baseline characteristics predicted future coronal caries progression over the 13 months of the study.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, some studies demonstrated that CHX elicits a low efficacy in the treatment of severe periodontal diseases (36), or in the presence of coronal caries (37), if it is not associated to a mechanical removal of bacterial plaque. It is likewise important to emphasize that in the presence of advanced periodontal disease the use of CHX could result not sufficient to improve the periodontal condition, if not associated with subgingival treatment (38).…”
Section: A Comparative Randomized Controlled Study On Clinical Effimentioning
confidence: 99%
“…On the other hand, it has been demonstrated the possibility of interaction and mutual inactivation of chlorhexidine and toothpaste that contains a common detergent compound, sodium lauryl-sulfate (38). Therefore, we recommend the use of CHX after an interval of 30 minutes by the use of other products for oral hygiene.…”
Section: A Comparative Randomized Controlled Study On Clinical Effimentioning
confidence: 99%
“…Consequently, there is no strong clinical evidence supporting the long-term prevention of re-infection of cariogenic bacteria and very few studies examining the impact on caries reduction (Milgrom et al, 2009;Vollmer et al, 2010;Young et al, 2010;Papas et al, 2012). The reason for the lack of long-term protection could be tied to the persistence of cariogenic bacteria within the dental plaque and the dynamic balance of the biofilm community between a healthy state and cariogenic state.…”
mentioning
confidence: 99%